The Supply Chain Analysis of Traditional Fish Catches of Bagan Deli City Medan and Bagan Percut of Deli Serdang District: Supply chain analysis - Andri Nasution; Tania Alda (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2023)
Traditional fishermen are fishermen who catch fish in waters which are traditional fishing rights that have been used for generations by local culture and wisdom. Fish is a marine product that is easily damaged or perishable, and this is due to enzymatic activity in the fish's body and the activity of microorganisms due to wrong handling. The cities of Medan and Deli Serdang are areas that have good potential for marine products. Enjoying fish products from the sea by consumers, fish distribution was carried out at Belawan Port, precisely at Belawan Ocean Fisheries Port and Fish Auction Place Bagan Percut, Deli Serdang. This study looks at the supply chain or supply chain for traditional fishermen in the North Sumatra region, especially in Medan City and Deli Serdang Regency. The research method used is descriptive qualitative research. The results of the study found that the supply chain of most fishermen caught in Bagan Deli through agents and distributors of fish was then brought to the market or auction place. There are also fishermen in Bagan Deli who directly sell their catch at the local market where the fishing group is located, namely the Bagan Deli and Belawan Traditional Markets. Meanwhile, Bagan Percut of Deli Serdang Regency shows that the role of fish agents and distributors in the supply chain of capture fishermen is very influential. Through these fish agents and distributors, distribution channels can be determined based on the amount or amount of fish caught.